The influence of experience marketing, sense of virtual community, and satisfaction on user purchase intention in live stream sales - Yu-Liang Feng; Ya-Qin You; Shing-Sheng Guan; Zhen-Ning Yuan; Xiao-Yue Chen (PLoS ONE, 2025)
Amid the digital and mobile internet boom, Live Stream Sales has emerged as a transformative, contactless commerce model reshaping consumer behavior. This study examines how diverse user experiences influence Sense of Virtual Community, Satisfaction, and Purchase Intention. The results indicate that think, act, and relate experiences significantly enhance satisfaction; feel and act experiences directly promote purchase intention; and both sense of virtual community and satisfaction serve as key mediators in driving purchase intention. These findings deepen the understanding of user experience in live commerce and provide practical guidance for enhancing consumer engagement and purchase motivation.